2019
DOI: 10.1063/1.5122260
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of a vortex ring caused by its impingement on a sphere

Abstract: The deformation of a vortex ring caused by its impingement on a sphere was numerically investigated using a proposed vortex-in-cell method. The method was validated by simulation of the collision of a vortex ring with a rigid planar surface and proved to be most satisfactory in the analysis of the dynamics of a vortex structure. In a coaxial collision, the behavior of the vortex structure is similar to that in the case of a planar surface. A secondary vortex ring is formed owing to the separation of the bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In contrast, vortex-ring collisions upon round solid boundaries such as spheres, convex/concave walls or round cylinders have received significantly less attention as the above vortex-ring collision configurations. Nguyen et al (2019) conducted both experiments and simulations on vortex-ring collisions upon a round sphere, where the sphere diameter was 3 times the orifice size. The effects of lateral offset between the vortex-ring and sphere were investigated as well and results showed that coaxial collisions are relatively two-dimensional, while non-coaxial collisions led to nonuniform circulation of the primary vortex-ring and more three-dimensional resulting flow structures and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, vortex-ring collisions upon round solid boundaries such as spheres, convex/concave walls or round cylinders have received significantly less attention as the above vortex-ring collision configurations. Nguyen et al (2019) conducted both experiments and simulations on vortex-ring collisions upon a round sphere, where the sphere diameter was 3 times the orifice size. The effects of lateral offset between the vortex-ring and sphere were investigated as well and results showed that coaxial collisions are relatively two-dimensional, while non-coaxial collisions led to nonuniform circulation of the primary vortex-ring and more three-dimensional resulting flow structures and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Allen et al (2007), only a secondary vortex ring was observed to form. In the more recent study by Nguyen et al (2019) where the diameter of the sphere is much larger, at three times the vortex ring orifice, formations of secondary and tertiary vortex rings after the primary vortex ring collides with the sphere coaxially can be observed. However, experimental and numerical flow visualizations were presented only up to a non-dimensionalized time t * = 0.917, and subsequent interactions between the three different vortex rings were lacking.…”
Section: Introductionmentioning
confidence: 92%
“…Other than convex cylindrical surfaces, there are other curved geometries that are of interest, but one that is of particular interest here involves hemispheric surfaces. Several past works studied coaxial vortex ring collisions with full spheres and shed much light on how the formations of vortex ring structures differ from those associated with planar geometries due to inherent differences between the pressure gradients and boundary layers of planar and spherical surfaces, as well as how non-coaxial collisions will affect the vortex dynamics (Allen, Jouanne & Shashikanth 2007; Ferreira de Sousa 2012; Nguyen, Takamure & Uchiyama 2019). In the study by Allen et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cottet and Koumoutsakos [13] combined it with a viscous model to simulate two-and three-dimensional incompressible viscous flows. A VIC method was developed to simulate the flow around two tandem cylinders, the flow around four cylinders of various shapes, and the vortex−wall interaction by Nguyen et al [14][15][16]. It was proven that the method could capture the vortex shedding, the interaction between the vortex wakes, the fluid forces exerted on the cylinders, and the vortex formation and deformation due to the wall effects.…”
Section: Introductionmentioning
confidence: 99%